There’s more to overeducation than a wage penalty: A systematic review of 2011–2021 literature on a vertical job-education mismatch in Europe - Krzywda-Starzyk, Patrycja (Kultura-Społeczeństwo-Edukacja, 2024)
A massive expansion of education – notably tertiary – has been one of the defining features of the late 20th and early 21st centuries. In parallel, a phenomenon of overeducation emerged as part of employees have been working in jobs below their educational attainment. Current overeducation literature lacks a clear articulation of different contexts that the mismatch is discussed in. Traditionally, the debate about the mismatch has been dominated by the human capital view and focused on its incidence and wage penalty. Acknowledging a broader vision of education and its role, this paper shifts the attention to research directions other than the two fundamental issues. Building on a systematic review of 2011–2021 literature, 11 research lines of overeducation research in Europe were identified and discussed. Results reveal that the 2011–2021 research was focused mainly on migration, persistence, and job satisfaction out of the 11 themes. New research lines were identified and major methodological contributions to existing ones were noted such as using capabilities approach as theoretical framework to assess the interplay between overeducation and well-being. The review also highlights that individual characteristic and a broadly understood environment of the individual impact the risk of entering the mismatch and its consequences. The review provides a fresh perspective on overeducation, emphasizing its complexity and capturing nuances.